Professionalism of Islamic Religious Education Teachers in Creating Evaluation Instruments Using the Written Test Method at the Qur'anic Literacy Elementary School - Suriyanti; Sri Hartati; Mirzon Daheri; Deri Wanto (CV Media Inti Teknologi, 2023)
This study aims to explore the professionalism of Islamic Religious Education teachers in creating evaluation instruments using the written test method at Qur'anic Literacy Elementary Schools. The approach used is a qualitative approach. Data collection methods include observation, interviews and documentation. The results of the research show that the professionalism of teachers, especially in Qur'anic Literacy Elementary Schools, is good because in the middle of the semester the teachers carried out evaluations by making 2 types of written test questions. A. Category of written test questions for children who are not yet fluent in reading. B. Question category for children who are already fluent in reading. One of the most important components in learning is evaluation. With evaluation, teachers can quickly determine the level of success of students in participating in the learning activities that have been carried out. Evaluations are also carried out to evaluate student progress in learning.